2005
DOI: 10.1002/ana.20724
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and alpha brain rhythms in mild cognitive impairment: A multicentric Electroencephalogram study

Abstract: Objective: Relationships between the apolipoprotein E 4 allele and electroencephalographic (EEG) rhythmicity have been demonstrated in Alzheimer's disease (AD) patients but not in the preclinical stage prodromic to it, namely, mild cognitive impairment (MCI). The present multicentric EEG study tested the hypothesis that presence of 4 affects sources of resting EEG rhythms in both MCI and AD subjects. Methods: We enrolled 89 MCI subjects (34.8% with 4) and 103 AD patients (50.4% with 4). Resting eyes-closed EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 133 publications
12
88
1
Order By: Relevance
“…Recent evidence suggests that genetic factors of pathological aging like clusterin ( CLU ) gene polymorphisms and the apolipoprotein E ε4 ( APOE4 ) mutation may affect upper alpha absolute power in nondemented elderly individuals [27], or reduce the amplitude of the posterior-dominant alpha rhythm in early AD [28, 29]. Taken together, these alpha frequency findings suggest that the genotype is associated with age-related preclinical dysregulation of hippocampal function and contributes to AD pathophysiology.…”
Section: Aging and Cortical Oscillationsmentioning
confidence: 71%
“…Recent evidence suggests that genetic factors of pathological aging like clusterin ( CLU ) gene polymorphisms and the apolipoprotein E ε4 ( APOE4 ) mutation may affect upper alpha absolute power in nondemented elderly individuals [27], or reduce the amplitude of the posterior-dominant alpha rhythm in early AD [28, 29]. Taken together, these alpha frequency findings suggest that the genotype is associated with age-related preclinical dysregulation of hippocampal function and contributes to AD pathophysiology.…”
Section: Aging and Cortical Oscillationsmentioning
confidence: 71%
“…Delta power is usually believed to increase only in more severe stages of the disease (Jeong 2004). However, several studies also reported an increase in delta power in MCI patients when compared with healthy aged controls (see, for example, Babiloni et al 2006aBabiloni et al , b, 2010Rossini et al 2008). Moreover, Fernandez et al (2006c) demonstrated than MCI patients with elevated delta activity in posterior parietal regions had a significantly elevated risk of conversion to AD.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is reported in the following. Firstly, we selected the standard fixed frequency bands in line with previous field studies of our research group [14,[32][33][34][35], namely delta (2-4 Hz), theta (4-8 Hz), alpha1 (8.5-10 Hz), alpha2 (10.5-13 Hz), beta1 (13.5-20 Hz), beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-40 Hz). Secondly, eLORETA solutions using the following fixed frequency bands were computed.…”
Section: Control Analysismentioning
confidence: 99%
“…LORETA estimation unveiled a positive correlation between activities in the posterior cortical regional sources of low-frequency alpha rhythms (8-10.5 Hz) and the global cognitive status in Nold, ADMCI, and ADD subjects as a whole group; in contrast, that correlation was negative for occipital cortical sources of the delta rhythms [14,[32][33][34]. Compared to the groups of Nold and ADD subjects, the PPD group exhibited a higher activity in the central delta and posterior theta sources, besides a lower activity in the posterior beta sources [35].…”
Section: Introductionmentioning
confidence: 98%